Porous " brick-like" NiFe2O4 nanocrystals loaded with Ag species towards effective degradation of toluene - Zhu, Z.; Li, Xin Yong; Zhao, Q.; Li, H.; Shen, Y.; Chen, G. (Elsevier BV, 2010)
Porous and " brick-like" NiFe2O4 nanoparticles were synthesized by a modified chemical co-precipitation route with calcination temperatures of 773K, 873K and 973K, respectively. The Ag/NiFe2O4 catalyst was prepared based on the porous NiFe2O4 by the incipient wetness impregnation strategy, which showed excellent photoelectric property and catalytic activity. The structural properties of these samples were systematically investigated by X-ray powder diffraction (XRD), scanning electronic microscopy (SEM), energy-dispersive X-ray spectra (EDX), UV-vis diffuse reflectance spectroscopy (DRS), and Fourier transform infrared spectroscopy (FT-IR) techniques. The photo-induced charge separation in the samples was demonstrated by surface photovoltage (SPV) measurement. The photocatalytic degradation of toluene by the Ag/NiFe2O4 and NiFe2O4 samples was comparatively studied under xenon lamp irradiation. The results indicate that the Ag/NiFe2O4 sample calcined at 773K exhibited the highest efficiency for the degradation of toluene. © 2010 Elsevier B.V.